The baffled parent’s guide to coaching girls’ soccer - Hounsome, Drayson (Ragged Mountain Press, 2005)
Don't despair—Coaching Girls' Soccer is here to help. From your first team meeting to the season-ending pizza party, Coaching Girls' Soccer will get you started and keep you going. In addition to learning how to teach the fundamental skills of passing, dribbling, heading, and shooting, you'll learn how to encourage competition and athleticism in girls, how to build their confidence and self-esteem, and how to deal with performance changes as girls mature. You'll even develop the coaching style that works best for you and your players. Before you know it, you'll be coaching players who are moving, motivated, and most of all, having fun.